Pengaruh Literasi Keuangan Syariah, Persepsi Risiko, Sikap, Norma Subjektif, Dan Persepsi Kendali Perilaku Terhadap Minat Berinvestasi Emas - Dela Akira Rimadani; Ach. Yasin (ITB AAS INDONESIA Surakarta, 2026)
The low interest of Generation Z in gold investment is a contradictory phenomenon amid increasing investment awareness and easy access to investment platforms in Indonesia, especially in East Java, with has the second-largest Generation Z population in Indonesia. This study aims to analyze the influence of Islamic financial literacy, risk perception, attitudes, subjective norms, and perceived behavioral control on the interest in gold investment of Generation Z in East Java. This study uses a quantitative approach with primary data collected through questionnaires and analyzed using SEM-PLS (SmartPLS3). The results of the study indicate that the variables of Islamic financial literacy, risk perception, attitudes, subjective norms, and perceived behavioral control significantly influence Generation Z's interest in gold investment of Generation Z in East Java. Therefore, the government, financial institutions, and investment service providers should design more effective Islamic financial education programs or risk management for Generation Z, in order to encourage interest in gold investment.